The impact of technology-mediated scaffolding on the development of EFL learners' speaking components. El impacto del andamiaje mediado por tecnología en el desarrollo de los componentes de habla de los estudiantes de inglés como lengua extranjera - Neda Abedi (Universidad de Las Palmas de Gran Canaria, 2022)
The present study attempted to survey the effect of technology-mediated scaffolding on the development of second language speaking components (fluency, coherence, lexical resources, grammatical range, and accuracy, and pronunciation) among Iranian intermediate EFL adult learners. To do so, 60 intermediate level female students with the age range of 18 to 25 in the EFL research center in Tehran were selected from among 90 intermediate students according to their performance in a standard version of the Preliminary English Test (PET). The selected participants were divided into two groups, namely the experimental group (EG) in which the learners received technology-mediated teaching through Telegram application, and the control group (CG), who followed the conventional teaching/learning methods of L2 speaking. The participants went through the process of pre-testing, intervention, and post-testing. Then, the data collected were analyzed, and multivariate ANOVA (MANOVA) was run to probe the null-hypotheses. The outcome of the post-test data analyses clarified that technology-mediated scaffolding had a statistically significant effect on the speaking sub-skills such as fluency, lexical resource, grammatical range and accuracy, and pronunciation of Iranian EFL learners.